Improving the Standards-Based Management-Recognition initiative to provide high-quality, equitable maternal health services in Malawi: an implementation research protocol - Mumtaz, Zubia; Salway, Sarah; Nyagero, Josephat; Osur, Joachim; Chirwa, Ellen; Kachale, Fannie; Saunders, Duncan (BMJ Global Health)
Background: The Government of Malawi is seeking evidence to improve implementation of its flagship quality of care improvement initiative—the Standards Based Management-Recognition for Reproductive Health (SBM-R(RH)). Objective: This implementation study will assess the quality of maternal healthcare in facilities where the SBM-R(RH) initiative has been employed, identify factors that support or undermine effectiveness of the initiative and develop strategies to further enhance its operation. Methods: Data will be collected in 4 interlinked modules using quantitative and qualitative research methods. Module 1 will develop the programme theory underlying the SBM-R(RH) initiative, using document review and in-depth interviews with policymakers and programme managers. Module 2 will quantitatively assess the quality and equity of maternal healthcare provided in facilities where the SBM-R(RH) initiative has been implemented, using the Malawi Integrated Performance Standards for Reproductive Health. Module 3 will conduct an organisational ethnography to explore the structures and processes through which SBM-R(RH) is currently operationalised. Barriers and facilitators will be identified. Module 4 will involve coordinated co-production of knowledge by researchers, policymakers and the public, to identify and test strategies to improve implementation of the initiative. Potential impact: The research outcomes will provide empirical evidence of strategies that will enhance the facilitators and address the barriers to effective implementation of the initiative. It will also contribute to the theoretical advances in the emerging science of implementation research.
This is an Open Access article distributed in accordance with the Creative Commons Attribution Non Commercial (CC BY-NC 4.0) license, which permits others to distribute, remix, adapt, build upon this work noncommercially, and license their derivative works on different terms, provided the original work is properly cited and the use is non-commercial. See: http:// creativecommons.org/licenses/by-nc/4.0
Keywords: Malawi; Standards Based Management-Recognition for Reproductive Health (SBM-R(RH)); Policymakers; Programme managers; Reproductive Health; Ministry of Health (MOH); Emergency obstetric care (EmOC)